UPAYA INDONESIA MENINGKATKAN DAYA SAING MUSLIM FRIENDLY TOURISM (MFT) DIANTARA NEGARA-NEGARA OKI - Komalasari, Intan; ", Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research explains Indonesia's efforts to improve competitiveness advantage of Muslim Friendly Tourism (MFT) between the OIC countries. The expenditures of Muslim tourists spending was USD 145 Billion in 2014 and is estimated to be USD 200 Billion in 2020. This lucrative prospect shall encourage many countries of the world to be a main actor in this industry particularly the OIC member countries to work on MFT professionally, including Indonesia. Indonesia has abundant muslim friendly destinations and potential resources to be developed more in order to atract international tourist and gain fruitful national income. on the contrary by those facts, Indonesia's position remains in Group B which defines as the best position for growth under anothe members of OIC MFT developer countries.The author has collected data from various resources predominantly TP3H and COMCEC to analyze Indonesia's efforts to improve its MFT competitiveness advantage. The theoretical framework used in this study is the perspective of realist-mercantilism, nation-state as unit analysis, the concept of national economic interests, the theory of competitive advantage.This study demonstrates that Indonesia’s efforts to enhance its MFT competitiveness advantage between OIC member countries is proven to be as competitive one measured by progressive quality development regarding to MFT competitive advantage (ca) through the main components such key faith-based needs, demand side key themes, supply side key themes.Keywords: Muslim Friendly Tourism (MFT), Competitive Advantage (CA) Indonesia, Organization of Islamic Cooperation (OIC)